Avaliação de limiar e máximo conforto auditivo por meio de procedimentos operantes com crianças surdas prélinguais submetidas a implante coclear - Silva, Wagner Rogério da (2005)
The cochlear implant is a prosthetic electric device that is implanted through surgery. I has the propose of substituting the cochlear functions allowing thus, the individuals with pre and post-linguistic neurosensorial deafness to begin to detect environmental sounds. One of the necessary procedures to help someone to develop hearing skills after the implant is to trace electrodes, which is a procedure that basically consist of determining measures of threshold and maximum hearing comfort for each implanted electrode. In order to obtain these within the clinical practice, the oral skills of the individuals with implant must be considered. The precision of these measures become very compromised among implanted children with pre-linguist deafness, due to the deficit of their speech capacity. The purpose of the present study is to propose an evaluation of two procedures that attempt to obtain measures of both, hearing threshold and maximum hearing comfort without using neither, directions or verbal answers. The study consist de two experiments composed by seven pre-linguist children with profoundly neurosensorial deafness, which have acquired the Nucleus 24® cochlear implant system . In one of de procedures, a simple operant discrimination between the presence and absence of de hearing stimulus was established during the training phase. Following, a testing phase was introduced in order to determine the hearing threshold to assess the discrimination loss through a descendant scale, which measures the variation intensity of the electric stimulus (Experiment 1). In the other procedure, it was established that during the electric stimulation of the training phase, an answer could stop the stimulus while no answer produce a positive reinforcement. Next, the intensity of the stimulus was modified during the test phase in ascendant scales with or without an answer, in order to determine whether or not the stimulus was comfortable to the subject (Experiment 2). In both procedures, the electric stimulation was realized through an electrode located in the cochlear medial region. Electro-physiologic measures of the ECAP and ESR were evaluated in an additive form within the same date that the operational procedures were realized. Also, measures of the hearing threshold obtained during clinical approach of the last evaluation, preceding the beginning of the experiments, were registered. All of these measures were compared to results obtained from de operant procedures. The results demonstrated in the Experiment 1, all of the participants learned the taught discrimination and how to use this skill during the variation of the electric stimulation in descendant scales. This experiment was also used to indicate hearing threshold measures with consistence to all of the participants. In the Experiment 2, five of the seven participants mastered the procedure; however, the results indicate that the order two participants learned that the answer would interrupt an electric stimulus and its absence would lead to the reinforcement. Thus, their performance aimed for identification of the consistence level of the maximum comfort in ascendant scales of variation. The training phase was not successful with the other participants, compromising then the consistence of the performance demonstrated during the testing phase; nonetheless, the measures are suggested for them as well. Concerning the relationship among the operant measures and the other measures betaken in the study, the results show that measures of operant threshold are similar to or smaller than the measures obtained through clinical methods. Regarding the maximum comfort values as the most relevant data. It has been emphasized that the two participants that fulfilled the expected performance in the procedure, demonstrated stapedial reflex values (ESR) similar to the obtained from operant form. The data suggest initial evidence that the operant procedure can contribute to the realization of tracing electrodes with larger precision among pre-linguistic children with implants.